Canine circovirus among dogs and cats in China: first identification in cats - Xiao, Xiangyu; Li, Yan chao; Xu, Feng pei; Hao, Xiangqi; Li, Shoujun; Zhou, Pei (Frontiers in Microbiology, 2023)
Canine circovirus (CanineCV) is a virus associated with respiratory and digestive diseases in dogs and often occurs in coinfections with other pathogens, thereby aggravating the symptoms of infected dogs. CanineCV was first reported in the United States in 2012. Subsequently, it was reported among dogs in Europe, Asia, and South America. To investigate the prevalence of CanineCV in dogs in China, 331 dog samples were collected in this study. The PCR results showed that 9.06% (30/331, 95% CI=6.2%~12.7%) of the dog samples were CanineCV positive. CanineCV has also been detected in some carnivorous wild animals, indicating the potential risk of cross-species transmission of this virus. And, cats are also one of the most common pets in our daily lives, who is close contact with dogs. Thus, this study first investigated the prevalence of CanineCV in cats. The PCR results showed that 3.42% (14/409, 95% CI=1.9%~5.7%) of the cat samples were CanineCV positive. Moreover, 14 canine-derived CanineCV whole genomes and the first cat-derived CanineCV whole genome were obtained in this study. Rep and Cap are the major nonstructural proteins and structural proteins of CanineCV, respectively. In nucleic acid homology analyses, these 15 CanineCV strains showed a high degree of variation in Rep (85.9~99%) and Cap (85.6~100%). In phylogenetic analyses, the 15 CanineCV strains clustered into 3 different genotypes (genotypes 1, 3, and 4). Among them, the first cat-derived CanineCV belonged to CanineCV-3. In addition, 4 genetic recombination events were predicted in these 15 CanineCV strains, occurring in multiple regions of the genome. In conclusion, this study is the first to provide evidence of CanineCV infection in cats and successfully obtained the first whole genome of cat-derived CanineCV. The complex circulation and high prevalence of CanineCV among dogs and cats emphasize the importance of continuous monitoring of this virus in various animal species.